Chat, Chunk and Topic in Casual Conversation - Vogel, Carl (My University, 2018)
Casual conversation does not follow a highly interactive ‘ping-pong’ structure but rather develops as a sequence of ‘chat’ and ‘chunk’ phases. Chat phases are highly interactive stretches amenable to Conversation Analysis, while chunk phases present as longer monologic stretches where one speaker dominates. Chunk phases can often be described in terms of genre, often manifesting as narrative. We describe an annotation scheme for chat and chunks, the chat and chunk annotation performed on six long (c. 1 hour) multiparty casual conversations, and outline plans to compare these chat and chunk annotations to topic annotations on the same data.
Proceedings 14th Joint ACL - ISO Workshop on Interoperable Semantic Annotation
PUBLISHED
Sante Fe, NM, USA
Keywords: Digital Humanities; DIALOG; Discourse & Dialogue; computational linguistics